HISTORY OF WOMEN’S ACTIVITIES IN LIGHT INDUSTRY OF UZBEKISTAN - Akramova, Fazilat (Current Research Journal of History, 2021)
This article provides a detailed overview of the role and importance of women's participation in the light industry of Uzbekistan. The history of human society is unthinkable without light industry. With the development of a person, his needs grew, and in particular his needs for clothes, shoes, fabrics. The textile, sewing, leather and fur and footwear industries developed. The impetus for industrialization and the development of capitalism was the development of textile production.